The Influence of Relationship Marketing among Franchisee and Franchisor in Fried Chicken Local Franchise - Rusman Rusni Fitri Y; Ikawati Karim (University of Sang Bumi Ruwa Jurai, 2017)
The increase of chicken production and consumption has a positive impact on the growth of chicken meat business as main product namely fried chicken local franchise. To maintain this domestic business, relationship among franchisee and franchisor should bond each other. This kind of relationship are explained on relationship marketing theory which has several mediators such as commitment, trust, relationship satisfaction and relationship quality. Therefore, this study aimed to examine the influence of these four relationship marketing mediators among franchisee and franchisor in one of fried chicken local franchise in South Sulawesi. Data were collected through observations and questionnaires from 38 franchisees and analyzed with path analysis. The results of paths standard coefficient value indicated that trust had a significant effect to commitment by 0,79 while trust together with commitment also had significant effects to relationship satisfaction by 0,37 and 0,50. Thus, commitment and relationship satisfaction also had significant effect to relationship quality. However, trust had low effect to relationship quality with just 0,247. These results showed that trust, commitment, relationship satisfaction are strong keys to develop the relationship between franchisee and franchisor in order to support local franchise while relationship quality still need some improve from trust side between franchisee and franchisor.